GLÜCK, Helmut (Hrsg.). Metzler Lexikon Sprache. Stuttgart, J.B.Metzler, 2000. XXXVIII+817 p. - Miranda, Félix Bugueño (Organon, 2012)
GLÜCK, Helmut (Hrsg.). Metzler Lexikon Sprache. Stuttgart, J.B.Metzler,2000. XXXVIII+817 p.Resenhado por: Félix Bugueño Miranda